A Study on Securing Privacy In Personalized Web Search (International Journal of Engineering and Computer Science, 2017)
Millions of users wants to get some information on web search engines. The growing use of search engines enables us to mainly describe the information that we seek. However, the major pitfall of generic search engine is that they returns the same list of results to user which can be irrelevant for users need. To address these problem, personalized search is considered to be encouraging solution as it provides relevant search results as per users information need and interest. We study securing privacy in PWS which captures user personal information and generates user profile and outputs relevant list of results. For web searching, user profiles are must for effective results. But the use of this profile to find interest is a breach to secure privacy. To conquer this issue, securing privacy is necessary. Hence, we study the existing methods for security of privacy in personalized web search and its efficacy.